Initial-site characterization of hydrogen migration following strong-field double-ionization of ethanol - Travis Severt; Eleanor Weckwerth; Balram Kaderiya; Peyman Feizollah; Bethany Jochim; Kurtis Borne; Farzaneh Ziaee; Kanaka Raju P; Kevin D. Carnes; Marcos Dantus; Daniel Rolles; Artem Rudenko; et al. (Nature Communications, 2024)
Abstract An essential problem in photochemistry is understanding the coupling of electronic and nuclear dynamics in molecules, which manifests in processes such as hydrogen migration. Measurements of hydrogen migration in molecules that have more than two equivalent hydrogen sites, however, produce data that is difficult to compare with calculations because the initial hydrogen site is unknown. We demonstrate that coincidence ion-imaging measurements of a few deuterium-tagged isotopologues of ethanol can determine the contribution of each initial-site composition to hydrogen-rich fragments following strong-field double ionization. These site-specific probabilities produce benchmarks for calculations and answer outstanding questions about photofragmentation of ethanol dications; e.g., establishing that the central two hydrogen atoms are 15 times more likely to abstract the hydroxyl proton than a methyl-group proton to form H $${}_{3}^{+}$$ 3 + and that hydrogen scrambling, involving the exchange of hydrogen between different sites, is important in H2O+ formation. The technique extends to dynamic variables and could, in principle, be applied to larger non-cyclic hydrocarbons.